The Position of Heirs Born to Parents of Different Religions According to Balinese Customary Law - Kusumantara, I Komang Arya; Wesna, Putu Ayu Sriasih; Utama, I Wayan Kartika Jaya (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study analyzes the inheritance rights of children from interfaith marriages under Balinese customary law. It was found that children who followed the mother's religion only inherited from the mother's side, not from the father's side. This is supported by the decision of the Denpasar District Court Number 483/Pdt.G/2020/PN Dps, which states that non-Hindu children cannot inherit from their Hindu father's family. This study concludes that religious changes during marriage affect children's inheritance rights in Balinese customary law.